Effects of Fructus Chaenomelis on longitudinal bone growth in adolescent rats - Chung hun Lee; Do Yeon Lee; Ji Hoon Jeong; Tae Jin Lee; Eon Sub Park (International Journal of Phytomedicine, 2014)
Effects of Fructus Chaenomelis on longitudinal bone growth in adolescent rats